The human spindle assembly checkpoint protein Bub3 is required for the establishment of efficient kinetochore-microtubule attachments - Logarinho, Elsa (2008)
The spindle assembly checkpoint monitors the status of kinetochore-microtubule (K-MT) attachments and delays anaphase onset until full metaphase alignment is achieved. Recently, the role of spindle assembly checkpoint proteins was expanded with the discovery that BubR1 and Bub1 are implicated in the regulation of K-MT attachments. One unsolved question is whether Bub3, known to form cell cycle constitutive complexes with both BubR1 and Bub1, is also required for proper chromosome-to-spindle attachments. Using RNA interference and high-resolution microscopy, we analyzed K-MT interactions in Bub3-depleted cells and compared them to those in Bub1- or BubR1-depleted cells. We found that Bub3 is essential for the establishment of correct K-MT attachments. In contrast to BubR1 depletion, which severely compromises chromosome attachment and alignment, we found Bub3 and Bub1 depletions to produce defective K-MT attachments that, however, still account for significant chromosome congression. After Aurora B inhibition, alignment defects become severer in Bub3- and Bub1-depleted cells, while partially rescued in BubR1-depleted cells, suggesting that Bub3 and Bub1 depletions perturb K-MT attachments distinctly from BubR1. Interestingly, misaligned chromosomes in Bub3- and Bub1-depleted cells were found to be predominantly bound in a side-on configuration. We propose that Bub3 promotes the formation of stable end-on bipolar attachments.